Rare case of a duodenal de novo dedifferentiated gastrointestinal stromal tumour. Issue 5 (7th May 2021) - Shah, Pritik A; Babu, Raghavendra; Uthaiah, Sowmya B; Patil, Shekar
Abstract : Gastrointestinal stromal tumours (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal tract. Dedifferentiation in these tumours occurs rarely, and when it does occurs most commonly after prolonged treatment with imatinib. We report the case of a 64-year-old man who presented with a mass of 8×7×3 cm dimensions involving the duodenum and head of the pancreas. On histopathology, areas of anaplastic tumour cells were negative for DOG-1, c-kit, CD-34, desmin and panCK along with a molecular level study showing wild-type KIT and PDGFRA (platelet-derived growth factor receptor alpha) gene. Based on focal GIST-like areas and CD117 positivity and absence of prior therapy, the diagnosis of a de novo dedifferentiated GIST was made. These tumours need to be reported as they pose a diagnostic challenge and their predicted response rated to targeted molecular therapies are unclear as compared with their c-kit positive counterparts.